THE INFLUENCE OF FIXED ASSETS INTENSITY, SALES GROWTH AND PROFITABILITY ON TAX AVOIDANCE ON REGISTERED AUTOMOTIVE COMPANIES ON IDX 2015-2018 PERIOD - Agustriana, Agustriana; Alpi, M. Firza (International Proceeding of Law and Economic; 2020: International Proceeding of Law and Economic, 2022)
The purpose of this study was to determine the effect of fixed asset intensity on tax avoidance, to determine the effect of sales growth on tax avoidance, to determine the effect of profitability on tax avoidance and to determine the effect of fixed asset intensity, profitability and sales growth on tax avoidance in automotive companies listed on the BEI. The research approach uses associative quantitative. The population in this study are all automotive companies listed on the IDX, where the number of companies is 11 companies and the sample from the study is 11 companies with 4 years of observation. The data collection technique used in this research is documentation. The analytical technique used in this research is descriptive statistics, Multiple Linear Regression analysis, Hypothesis Testing, Determinant Test. The results showed that partially fixed asset intensity had no effect on tax avoidance in automotive companies. Partially Sales Growth has no effect on Tax Avoidance, Partially has no effect on Tax Avoidance and Simultaneously shows that Fixed Asset Intensity, Sales Growth and Profitability have no significant effect on Tax Avoidance in Automotive Companies.